Bankruptcy Prediction of Software Companies Using Altman Z-Score - Mittal, Ruby; Singh, Netra Pal (Celebes Scholar pg, 2025)
This study employs a modified Altman Z-Score model to 15 selected companies with the aim to predict bankruptcy risk in the Indian software industry. Working capital to total assets, retained earnings to total assets, earnings before interest and taxes to total assets, and market value equity to book value of total liabilities, aside to the variable sales to total assets ratio, are the four main financial ratios used in the model, which is being altered for non-manufacturing businesses. The analysis is supported using secondary data from 2004 to 2022 that has been collected from financial statements and reliable financial websites. The study classifies businesses according to their financial stability via bibliometric analysis, descriptive quantitative approaches, and cluster analysis. Variations in 3i Infotech consistently displayed signs of financial distress, while companies include Mphasis, Tech Mahindra, and NIIT occasionally fell into a grey area, suggesting intermittent financial uncertainty, the majority of companies stayed in the non-distress group from 2004 to 2021, indicating a low bankruptcy risk. The study suggests the implementation of specific corrective measures, such as comprehensive financial restructuring and better risk-management methods, for businesses that have been identified to be in the distress and grey zones. In addition, to reduce the risk of bankruptcy and ensure long-term financial stability, proactive processes for governance and ongoing monitoring are encouraged.